After Shaming Aung San Suu Kyi: Then What? - Kang, Siew Kheng (2017)
While the UN has described the latest atrocities in Myanmar on the Rohingya minority as textbook ethnic cleansing, the international reaction of shaming Aung San Suu Kyi for the Rohingya crisis is unhelpful to all parties. ASEAN should consider coordinating action to help Myanmar overcome the complex problem.